The mythic voice of Statius : power and politics in the Thebaid - Dominik, William J. (Mnemosyne, Supplements, 1994)
This is the first thematic study of Statius' Thebaid to be published in monograph form in English in the past twenty years. It examines in detail the thematic design and intent of the Thebaid and considers the question of its contemporary relevance. The book focuses on the central theme of power - how it is exercised on the supernatural and human levels and the consequences of its pursuit and abuse in terms of the human condition. An ensuing discussion explores the political undercurrents of the epic. This discussion is in four main parts: (1) 'Use and Abuse of Supernatural Power'; (2) 'Pursuit and Abuse of Monarchal Power'; (3) 'Consequences of the Abuse of Power'; and (4) 'Political Relevance to Contemporary Rome'. The views expressed represent a fundamental departure from previous studies and constitute a critical reassessment of the Thebaid . The provision of translations makes the book accessible to the Latinless reader.